Effects of drying-off procedure of ewes’ udder, with intramammary antibiotic administration, in subsequent mammary infection and development of mastitis - PETRIDIS (Ι.Γ. ΠΕΤΡΙΔΗΣ), I. G.; MAVROGIANNI (Β.Σ. ΜΑΥΡΟΓΙΑΝΝΗ), V. S.; GOUGOULIS (Δ.Α. ΓΟΥΓΟΥΛΗΣ), D. A.; AMIRIDIS (Γ.Σ. ΑΜΟΙΡΙΔΗΣ), G. S.; BROZOS (Χ. ΜΠΡΟΖΟΣ), C.; FTHENAKIS (Γ.Χ. ΦΘΕΝΑΚΗΣ), G. C. (Journal of the Hellenic Veterinary Medical Society, 2017)
Objective of the study was to evaluate effects of the procedure followed for drying-off of ewes’ udder in subsequent mammary infection and development of mastitis, in an experiment, where intramammary antibiotic administration (procaine penicillin and neomycin) was performed into the right mammary gland of animals at end of lactation period. In ewes of group A, drying-off took place progressively during a period of 22 days; in ewes of group B, drying-off took place abruptly. Samples of teat duct material and milk for bacteriological and cytological examination were collected before start of the drying-off procedure and on two occasions after the subsequent lambing. Median time to first teat duct infection postpartum was 2 and 4.5 days (left and right, respectively) for group A and 6.5 and 3.5 days for group B (P > 0.38); median time to first mammary infection post-partum was 4.5 and 7 days (left and right, respectively) for group A and 6.5 and 3.5 days for groupB (P > 0.22). Principal bacterial isolates were coagulase-negative staphylococci. No significant differences were observed between the two groups in post-partum frequency of: teat duct infection (P > 0.17), mammary infection (P > 0.36), subclinical mastitis (P > 0.36), abnormal findings in a mammary gland (P > 0.17). No significant differences were seen between the two groups in post-partum incidence risk of the following outcomes: teat duct infection (P > 0.75), mammary infection (P > 0.42), subclinical mastitis (P > 0.39), abnormal findings in a mammary gland (P > 0.85). No significant differences were evident between the two groups in cure rate of abnormal findings in a mammary gland (P >0.89); a significant difference was evident between left and right mammary glands (P < 0.045). The results support a hypothesis that the procedure for udder drying-off (i.e., progressive or abrupt cessation of lactation) does not appear to affect the risk of subsequent mammary infection and development of mastitis, in cases of intramammary administration of antibiotics at the end of a lactation period. Intramammary administration of antibiotics improved cure rates of mammary abnormalities, independently of the procedure followed for udder drying-off.